Integrating Perspectives on the Certainty-Uncertainty Paradox. - Maroski, L. E. (ReVision)
The article focuses on the "certainty-uncertainty paradox," exploring the complex, interdependent relationship between certainty and uncertainty through philosophical, psychological, sociological, and linguistic perspectives. It highlights how certainty and uncertainty coexist, with each concept containing the other at its core, challenging the traditional view of them as linear opposites. The discussion includes epistemic certainty and uncertainty, unconscious and conscious dimensions, societal implications such as nuclear threats and misinformation, and the influence of language and metaphor on how these concepts are understood and communicated. The author advocates for developing new linguistic structures to better express and navigate this paradox, aiming to foster resilience and hope amid personal and collective uncertainties.